Implementasi Metode TGT (Teams Games Tournament) Dalam Pembelajaran Pendidikan Agama Islam Guna Meningkatkan Keaktifan Siswa Di Sekolah Menengah Kejuruan Al Masruroh Puger - Badrut Tamami (STIT Muhammadiyah Paciran Lamongan, 2022)
The teaching and learning model developed by Robert Slavin is the Teams Games Tournament, which is a learning method by combining study groups with team competitions, cant also be use improve learning various concept for skills (Silberman, 2006). Learning with this method will stimulate students' activeness, because in Teams Games Tournament all students are required to actively voice their opinions, both lower group students and upper group student are requiire at works togeether solving problems given in learning.The purpose of the implementation or application of the TGT method is none other than to increase student activity in absorbing and mastering the material presented in the teacheres on process teaching and learn activiti in Islamic Religious Education subjects at Al Masruroh Puger Vocational School, so that students do not experience boredom or boredom in receiving material using only the lecture method, the teams games tournament method is very appropriate and appropriate in overcoming students who are less active and are experiencing boredom for the teacher and learner progres.The author conducted research with a qualitatife aproach and a field study research methodology which directly observed, interviewed students, and in the observations the researchers found several changes in students, the first students were more active, the second students felt happy because they could learn while playing, the third students can collaborate with friends in solving problems, so that the time in the teaching and learning process feels less and not boring because all students are involved in all activities of providing material in class.